2004
DOI: 10.1117/1.1783897
|View full text |Cite
|
Sign up to set email alerts
|

Optical coherence tomography of malignancy in hamster cheek pouches

Abstract: Optical coherence tomography (OCT)/optical Doppler tomography (ODT) provides real-time in vivo high-resolution (10-microm) imaging of tissues and real-time spatially resolved blood flow in microvasculature. Hamster cheek pouches with induced dysplasia and malignancies were imaged with OCT/ODT to assess the potential for application to airway malignancy. In 22 Golden Syrian hamsters, 0.5% 9,10-dimethyl-1,2-benzanthracene induces carcinogenesis over 10 weeks in right side cheek pouches; the left side three serve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 13 publications
3
48
0
Order By: Relevance
“…18 In clinical trials, OCT endoscopes have been used in malignancies in different organs, including the gastrointestinal tract, larynx, esophagus, uterine cervix, colon, urinary bladder, and vascular, systems. [18][19][20] In this researches, it is shown that the alteration of intrinsic light scattering properties in tumor tissues make detection possible by OCT imaging, and can promote the clinical application of OCT technique.…”
Section: Discussionmentioning
confidence: 99%
“…18 In clinical trials, OCT endoscopes have been used in malignancies in different organs, including the gastrointestinal tract, larynx, esophagus, uterine cervix, colon, urinary bladder, and vascular, systems. [18][19][20] In this researches, it is shown that the alteration of intrinsic light scattering properties in tumor tissues make detection possible by OCT imaging, and can promote the clinical application of OCT technique.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] Previous studies using OCT have demonstrated the ability to evaluate characteristics of epithelial, subepithelial, and basement membrane structures and show the potential for near histopathological-level resolution and close correlation with histological appearance. [16][17][18][19][20][21][22][23][24][25][26][27][28][29] Two recent studies have reported the successful use of OCT for the early detection and quantification of radiation-and chemotherapy-induced mucositis in the mouse and hamster models. 30,31 In this feasibility study, the ability of OCT to detect and characterize chemotherapy-induced oral mucositis was evaluated in five human subjects.…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
“…Raman spectroscopy 97.44-100 77-100 (Li et al 2010;Guze et al 2015) Elastic scattering spectroscopy 72-98 68-75 (Jerjes et al 2004;Sharwani et al 2006b;Green et al 2014) Diffuse reflectance spectroscopy 76-100 76-97 (Mallia et al 2010;Jayanthi et al 2011;Stephen et al 2013) Narrow-band imaging 84.62-96 88.2-100 (Piazza et al 2010;Yang et al 2012b;Yang et al 2013;Shibahara et al 2014;Vu and Farah 2014;Yang et al 2014) Optical coherence tomography 73-100 78-98 (Matheny et al 2004;Wilder-Smith et al 2004;WilderSmith et al 2005;Wilder-Smith et al 2009;Olivo et al 2011;Hamdoon et al 2013;Green et al 2014) Confocal laser endomicroscopy 80 100 (Nathan et al 2014) Confocal reflectance microscopy 73 88 (Olivo et al 2011) Salivary biomarker miRNA-184 n/a n/a (Zahran et al 2015) IL-6 n/a n/a (Sharma et al 2011) oral cancer in 132 patients, and concluded that RB staining seemed promising for the detection of epithelial dysplasia in oral leukoplakia, lichen planus, and leukokeratosis (Du et al 2007). Zhang et al (2013) combined fluorescence spectroscopic techniques with RB staining to detect oral PMDs in an animal model in vivo and reported that the method showed excellent sensitivity.…”
Section: Chemiluminescencementioning
confidence: 99%